University Professors’ Attitudes Towards Implementing The Proposed Teaching Of "Digital Humanities" In Algerian Humanities Faculties: A Field Study On A Sample Of Professors In Humanities Disciplines At Algerian Universities - Mohamed Amine, BENCHARAD (Journal of Ecohumanism, 2025)
This research paper seeks to approach the attitudes of Algerian university professors towards teaching digital humanities (DH) in colleges of humanities, and encourage students in the graduate and postgraduate stages to employ DH in completing their research work, & by distributing a questionnaire to measure trends on a purposive sample of 242 professors working in one of the Algerian humanities colleges, and based on the Likert scale and adapting scattering scales, this field study concluded that professors have generally positive attitudes toward teaching digital humanities in humanities colleges, However, most of the respondents believe that Algerian higher education institutions did not take the extent of the changes occurring worldwide in academic research methods in the humanities disciplines into consideration and failed to keep pace with them.